Combination of electrical stimulation and bFGF synergistically promote neuronal differentiation of neural stem cells and neurite extension to construct 3D engineered neural tissue. (28th October 2020) - Meng, Xiao-ting; Du, Ying-shan; Dong, Zhi-yong; Wang, Guo-qiang; Dong, Bing; Guan, Xue-wa; Yuan, Yu-ze; Pan, He; Wang, Fang
Abstract: Objective . The construction of in vitro three-dimensional (3D) neural tissue has to overcome two main types of challenges: (1) How to obtain enough number of functional neurons from stem cells in 3D culture; (2) How to wire those lately developed neurons into functional neural networks. Here, we describe the potential of using direct current (DC) electric field (EF) together with basic fibroblast growth factor (bFGF) synergistically in promoting neural stem cell (NSC) neuronal differentiation following by directing neurite outgrowth in the 3D neural tissue construction. Approach . By adjusting the electrical stimulation setup in this study, long-term electrical stimulation could be present in vitro. At an EF strength of 150 mV mm −1, cell responses, including cell viability, neuronal differentiation, cell morphology, the length of neuronal processes, synaptic structure and neural network formation, were quantified and analyzed. Main results . Analysis revealed that NSCs showed no significant cell death after certain EF treatments. EF-stimulated NSCs in 3D Matrigel mainly differentiated into neurons, but unlike NSCs in two-dimensional conditions, their processes were flat and stunted. When combined with bFGF, EF stimulation provided appropriate bioactive cues to establish engineered neural tissue with a proper neuronal cell number, highly branched neurites, and a well-developed neuronal network. Significance . It is for the first time the synergistic effects of EF and bFGF stimulation have been evaluated in inducing the differentiation of NSCs into neurons and the acquisition of long neurites in a culture environment of in vitro 3D model. These optimized conditions may allow a well-developed neuronal network to be established within hydrogel droplets.